Failure to decolonize mupirocin and linezolid resistant MRSA from a patient with necrotizing soft tissue infection - Sumit Rai; Mayuri Rani; Debapriya D. Choudhury; Narendra P. Singh; Arun Gupta; Vikas Manchanda (Elsevier, 2016)
Summary: Colonization with methicillin resistant Staphylococcus aureus (MRSA) is considered to be a major risk factor for skin and soft tissue infections. We present a case of a patient suffering from necrotizing soft tissue infection and exposed to multiple antibiotics and developed colonization with linezolid resistant MRSA (LRMRSA). He could not be decolonized despite prolonged conventional or modified MRSA decolonization protocols. Keywords: Linezolid resistant MRSA, Decontamination, G2576U mutation